The Multiplicity of Post-Translational Modifications in Pro-Opiomelanocortin-Derived Peptides - Yasuda, Akikazu; Jones, Leslie S.; Shigeri, Yasushi (Frontiers in Endocrinology, 2013)
The precursor protein, pro-opiomelanocortin (POMC) undergoes extensive post-translational processing in a tissue-specific manner to yield various biologically active peptides involved in diverse cellular functions. The recently developed method of matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) for direct tissue analysis has proved to be a powerful tool for investigating the distribution of peptides and proteins. In particular, topological mass spectrometry analysis using MALDI-MS can selectively provide a mass profile of the hormones included in cell secretory granules. An advantage of this technology is that it is possible to analyze a frozen thin slice section, avoiding an extraction procedure. Subsequently, tandem mass spectrometry (MS/MS) has a profound impact on addressing the modified residues in the hormone molecules. Based on these strategies with mass spectrometry, several interesting molecular forms of POMC-derived peptides have been found in the fish pituitary, such as novel sites of acetylation in -melanocyte-stimulating hormone (MSH), hydroxylation of a proline residue in -MSH, and the phosphorylated form of corticotropin-like intermediate lobe peptide (CLIP).